If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(r + 2) = -24 Reorder the terms: 2(2 + r) = -24 (2 * 2 + r * 2) = -24 (4 + 2r) = -24 Solving 4 + 2r = -24 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2r = -24 + -4 Combine like terms: 4 + -4 = 0 0 + 2r = -24 + -4 2r = -24 + -4 Combine like terms: -24 + -4 = -28 2r = -28 Divide each side by '2'. r = -14 Simplifying r = -14
| 5m-14-6m=-13 | | 12/5+1/7t=3 | | 1a=3a-4 | | 15r=-50 | | 18-4t=10 | | x=4x-30 | | 21=18x | | x/8-7=-1 | | 2.7a-1.5=-5.64 | | 3(2x-6)-4=3(x-2)+8 | | (6r+3e-2d)+(3r-5e+3r)-(-5r+4e-8d)= | | k/8=10/12 | | -20s-3-25s-1=0 | | 21+(6/3)x8-1+35 | | 3u+36=-7(u-4) | | 1/6b=7.4 | | (6r+3e-2d)+(3r-5e+3r)-(-5r+4e-8d)= | | 3/p=-11/10 | | 11k+6=4k+34 | | f/-17=51 | | c=8d | | .17n=-51 | | x^2+30=11 | | 10/7=9/m | | 7(2)-2(2+6)=-2 | | 16k^2-9=0 | | X+6x(x+88)=40 | | 5/6=v/7 | | 3(4+x)=x+26 | | 67000*.09+x*.03=.04(67000+x) | | 2(w+3)+5=19 | | 6/12=x/2 |